Validation of a construct to determine the quality of tourism services - Calvopiña Andrade, Diego Mauricio (2019)
This study describes the validation of a construct to determine the quality of tourism services, which is regarded as the activity with the greatest global impact on political, economic, social, cultural, environmental and technological fields. This activity is no longer only based on the idea of the trip as it was previously understood. At present, it is increasingly oriented towards an active and participatory model, which suggests establishing innovative coexistence, learning and enjoyment strategies for both travelers and hosts. To this end, it is essential to consider services and their impact on competitiveness and sustainable development. The current trend of tourism is to place greater emphasis on the quality of tourism services as it is considered to be an essential part of the tourist experience, which raises the following question: what dimensions from the quality of tourism services construct (perceptions) influence tourism services? The validity and reliability of the instrument was determined, thus upholding its adequacy and the impact on tourism service quality criteria.